Cultivating academic success and inclusion: rethinking education for children with ADHD in Pakistan - Abbas, Syeda Qaima; Akhtar, Ahmad (Journal of the Pakistan Medical Association, 2024)
To the Editor, In Pakistan, 2.49% of children have ADHD, with a boy-to-girl ratio of 3:1(1). However, the challenge is exacerbated by a prevailing stigma surrounding mental health issues, which often compels potential individuals to shy away from seeking professional help. This predicament not only burdens these young minds but also gives rise to various complications as they transition into adulthood. (2) While some training sessions for teachers and parents have been conducted to address ADHD in Pakistan, the extent of these efforts remains limited. (3, 4) The merits of such initiatives are undeniable, as they empower caregivers to understand and adapt their behaviours to support affected individuals better. Moreover, educational institutions have an invaluable opportunity to evolve their teaching methodologies to cater to the unique mental constitution of children with ADHD. Once teachers are enlightened about the cognitive dynamics of their students, they can craft strategies to help these individuals maximise their academic potential. Guided by recommendations from the Attention Deficit Disorder Association (ADDA) (5), classroom settings can be tailored to assist atypical students facing academic challenges (refer to Table 1). Other practical suggestions include extending task submission deadlines for concerned students and rewarding those who meet them on time with extra credit. Similarly, allocating extra time during tests acknowledges the extra effort required by this population to accomplish tasks that come more easily to typical children. In this pursuit of curriculum adjustments, teachers must forge positive relationships with students dealing with ADHD. Creating an inclusive, nonjudgmental environment where students can freely express themselves without fear of criticism or reprimand is paramount. In summary, embracing innovative teaching methods that promote the inclusion of students with ADHD alongside their typical peers can yield profound benefits for their cognitive development, academic achievements, and social well-being. Providing these essential tools and fostering an inclusive learning environment empowers this young generation to navigate future challenges and lead fulfilling, independent lives.